Weak properties of circumscriptive logic programming - Fillottrani, Pablo Rubén (1997)
This is the second in a series of two papers in which we intend to study the formal properties of the semantics of Circumscriptive Logic Programs [6, 7]. The first one [8] was devoted to the strong properties [3], so called after its counterparts in nonmonotonic consequence relations [13, 20]. In this work we apply to this semantics the weak properties [4], specifically defined an extension of these principles to extended logic programs (they were originally defined for normal logic programs) and prove that the semantics of Circumscriptive Logic Programs is well-behaved [4, 5] in the sense it satisfies all “reasonable” principles.